Analysis of the Relationship between Perception of Workload and Job Stress on Nurse Performance in the Covid-19 Pandemic Era in the Covid Isolation Room of a Hospital in Mojokerto City - Zaenal, Zaenal; Datu, Natalia; Mustamin, Rini (Universitas Aisyah Pringsewu, 2024)
Workload and work stress are factors that affect the performance of a nurse. The low performance of nurses in the Covid isolation room at the hospital in the city of Mojokerto was due to the increase in the number of infected patients during the pandemic who were required to wear personal protective equipment, not balanced with the capacity of existing human resources , working hours that were more than working time did not even escape overtime hours so that nurses sometimes slept in the hospital, so that the provision of nursing care was not optimal. The purpose of this study was to analyze the relationship between perceptions of workload and work stress on the performance of nurses during the COVID-19 pandemic era in a hospital isolation room in the city of Mojokerto. Methods This research is a quantitative study with a descriptive analytical research design with a cross-sectional approach. With a sample of 67 respondents with a total sampling technique. Then tested with multiple linear regression and rank spearman using spss for windows 16.0. The results of the spearman rho test get the value of the two independent variables = 0.05, then H1 is accepted, meaning that there is a relationship between perceptions of workload and work stress with the performance of nurses in the Covid-19 isolation room. The results of the calculation of Multiple Regression there is a relationship between the variables of perception of workload and work stress of nurses with nurse performance. The conclusion is that there is a relationship between the workload and work stress of nurses and nurses' performance. To improve the performance of nurses, the hospital needs to pay attention to the conditions and work environment to be safe, comfortable, and conducive. This will help minimize the workload and stress experienced by nurses in carrying out their duties during the COVID-19 pandemic so that nurse performance can be more optimal.